Carbon materials on the basis of a coal coking byproducts - Kiselkov, D. M.; Moskalev, I. V.; Strelnikov, V. N. (Perm Federal Research Centre Journal, 2013)
An analysis of a wide variety of carbon materials that can be produced from hydrocarbon raw materials was carried out. The effectiveness of using coal coking byproducts for production of most carbon materials was proved. A new technology for production of non calcined pitch coke that can be used for high quality artificial graphites was developed. For approbation of this technology a pilot plant was built. The analysis of obtained experimental samples showed that at present the advantage of these cokes exceeds widely used cokes. A method for controlling main properties of cokes based on regulating the processes of generation and growth of mesophase was proposed.